2017
DOI: 10.1093/cercor/bhx266
|View full text |Cite
|
Sign up to set email alerts
|

A Modulatory Effect of Brief Passive Exposure to Non-linguistic Sounds on Intrinsic Functional Connectivity: Relevance to Cognitive Performance

Abstract: A growing literature on resting-state fMRI (R-fMRI) has explored the impact of preceding sensory experience on intrinsic functional connectivity (iFC). However, it remains largely unknown how passive exposure to irrelevant auditory stimuli, which is a constant in everyday life, reconfigures iFC. Here, we directly compared pre- and post-exposure R-fMRI scans to examine: 1) modulatory effects of brief passive exposure to repeating non-linguistic sounds on subsequent iFC, and 2) associations between iFC modulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…Prior work has shown that it has high test-retest reliability with only 5 min of rsFMRI data. 32 Furthermore, it has been linked to changes in local excitability and inhibition, 33 , 34 sensory learning, 30 , 35 , 36 , 37 and neurodevelopmental disability. 34 , 38 , 39 Thus, ReHo may be a promising marker of sensory cortex dysmaturity.…”
Section: Introductionmentioning
confidence: 99%
“…Prior work has shown that it has high test-retest reliability with only 5 min of rsFMRI data. 32 Furthermore, it has been linked to changes in local excitability and inhibition, 33 , 34 sensory learning, 30 , 35 , 36 , 37 and neurodevelopmental disability. 34 , 38 , 39 Thus, ReHo may be a promising marker of sensory cortex dysmaturity.…”
Section: Introductionmentioning
confidence: 99%
“…Both ReHo and fALFF have successfully detected regions associated with individual differences in cognitive abilities (S. Kuhn, Vanderhasselt, De Raedt, & Gallinat, 2014;Yang et al, 2015), clinical diagnoses/traits (Du, Liu, Hua, & Wu, 2019;Han et al, 2018;Hoexter et al, 2018;Respino et al, 2019;Xu, Zhuo, Qin, Zhu, & Yu, 2015;Xue, Lee, & Guo, 2018), and training/experience effects (Koyama, Ortiz-Mantilla, Roesler, Milham, & Benasich, 2017;Qiu et al, 2019;Salvia et al, 2019;Wu et al, 2019). However, to date, there are only a handful of studies that have applied these metrics to examination of achievement skills, IQ, and/or their relationships.…”
Section: Introductionmentioning
confidence: 99%
“…For arithmetic, Jolles et al (2016) compared a group of children with mathematical difficulties (i.e., lower arithmetic abilities) and the IQmatched control group, the first of which was characterized by higher fALFF in the intraparietal sulcus -a core region associated with number processing (Dehaene, Piazza, Pinel, & Cohen, 2003) and arithmetic (Bugden, Price, McLean, & Ansari, 2012;Dehaene, Molko, Cohen, & Wilson, 2004;Jolles et al, 2016;Menon, 2010). Regarding ReHo, no study has explored its whole-brain patterns associated with either achievement or IQ measures (but see Koyama et al, 2017 using a region of interest analysis).…”
Section: Introductionmentioning
confidence: 99%